Profile of Pediatric Rheumatic Heart Disease Patients with Mitral Regurgitation Receiving Angiotensin-Converting Enzyme Inhibitor in dr. Saiful Anwar General Hospital Malang - Faris Wahyu Nugroho; Ardian Rizal; Heny Martini; Indra Prasetya; Taufieq Ridlo Makhmud; Muhammad Saifur Rohman (Heart Science Journal, 2021)
AbstractBackground : Rheumatic heart disease (RHD) remains the leading cause of heart failure in children worldwide. Long-term consequences and sequelae of acute rheumatic fever may further contributes to isolated mitral regurgitation (MR), unless promptly treated, may develop to extensive fibrosis and calcification leading to mitral stenosis.  ACE inhibitor through reverse remodeling mechanisms may encounter secondary LV changes due to rheumatic MR. Studies in the field of RHD remain limited, particularly in Indonesia. Method : This observational descriptive study recruited 69 pediatric patients diagnosed with RHD who went to Pediatric Cardiology Clinic of dr. Saiful Anwar General Hospital during November 2018 to June 2019. A total of 22 patients were excluded due to incomplete data or showing no MR during echocardiography. The remaining samples (47 patients) were divided into two groups i.e: captopril and no captopril group. Data regarding profile of baseline characteristics, parameter of LV remodeling (dimension, mass and geometry), and grading of MR  were collected then tabulated using descriptive statistical analysis. Results : In general, from total 47 of sample population, female sex was found to predominate (68%), with mean age of 12.1 years and body mass index (BMI) 17.2 kg/m2. Proportion of distribution among captopril and no captopril group demonstrated no significant difference (p>0.05). Captopril group revealed younger age, higher BMI and longer time of initial RHD diagnosis compared to no captopril group. Evaluation of LV remodeling parameter demonstrated that captopril group had smaller LVIDd, lower LVMI, higher fractional shortening (FS) and higher LVEF. LVPWd dan RWT were found to be relatively similar among both groups. Evaluation of MR grade revealed that captopril group showed lower value of MR VC, MR EROA and MR regurgitant volume. Conclusion : Profile of pediatric RHD patients with MR who had been receiving captopril for at least 12 months in dr. Saiful Anwar General Hospital during period of 2018-2019 demonstrated younger age, higher BMI, smaller LVIDd, lower LVMI, lower MR grade, higher FS and higher LVEF compared to patients who had not. Keywords: rheumatic heart disease, mitral regurgitation, ACE inhibitor, captopril, left ventricle remodeling